Sintesis Nanopartikel Tembaga dari Larutan CuSO4.5H2O dengan Menggunakan Ekstrak Getah Merkubung ( Macarangan Gigantea) - Warni Warni; Restina Bemis; Diah Riski Gusti (Departemen Kimia FMIPA UNP, 2022)
The synthesis of copper nanoparticles in this study used a reducing agent from the extract of mercurd gum with a solution of CuSO4.5H20. The results of the synthesis of copper nanoparticles using the extract of mercurd gum resulted in the color of the solution becoming clear greenish. The reaction time greatly affects the formation of copper nanoparticles, it can be seen visually that after 5 minutes the reaction shows a color change from clear to clear greenish and a lot of precipitate is formed. As the reaction time increases, the solution gets darker. The color of the copper nanoparticle solution tends to be clear to clear greenish, the clear color will continue to increase with the length of reaction time. In XRD analysis of Cu which has been synthesized from 0.01 M mercury extract solution. It can be seen that Cu nanocrystals have been formed which are indicated by the appearance of peaks at 2q : 18.76˚, 22.24˚, and 23.99, The results of the Scanning Electron Microscopy analysis, the results of the SEM analysis in the study show that the particle sizes produced are different from one another and the distribution of particles is uneven, there are many particles that accumulate into chunks larger than other particles so that the size is not uniform and to form agglomerations. This is because the particle growth is very fast and UV-vis Confirmation of the formation of nanoparticles can be known through UV-Vis spectrophotometer observations by measuring the absorbance value in time intervals.